2020
DOI: 10.1002/hed.26234
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy during COVID‐19 pandemic—Novel approach

Abstract: Background: This study describes a novel approach in reducing SARS-CoV-2 transmission during tracheostomy. Methods: Five patients underwent tracheostomy between April 1, 2020 and April 17, 2020. A clear and sterile plastic drape was used as an additional physical barrier against droplets and aerosols. Operative diagnosis; droplet count and distribution on plastic sheet and face shields were documented.Results: Tracheostomy was performed for patients with carcinoma of tonsil (n = 2) and nasopharynx (n = 1), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 7 publications
1
37
0
1
Order By: Relevance
“…6,15,42e44,54 The most common barrier-enclosure types were plastic wraps or tents (25 reports), 5,9,12,15,17,23e29,31,33,34,38,39,41,42,44,46,47,52,54,56 acrylic aerosol boxes (19 reports), 4e6,8,11,15,16,18,19,22,24,35,36,43,45,51,53,57,58 and combinations of aerosol boxes and plastic wraps (eight reports). 6,8,13,15,32,37,43,49 Eleven reports included other types of barrier enclosures (modified incubator hood, 7 carton box, 8 acrylic panels, 50 surgical retractors, frames and anaesthetic poles, 21,42,44,48 external fixators, 14 suspension laryngoscopy support, 41,55 and modified packaging tray 40 ). In 10 cases, a smoke evacuator/aspirator was reported.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,15,42e44,54 The most common barrier-enclosure types were plastic wraps or tents (25 reports), 5,9,12,15,17,23e29,31,33,34,38,39,41,42,44,46,47,52,54,56 acrylic aerosol boxes (19 reports), 4e6,8,11,15,16,18,19,22,24,35,36,43,45,51,53,57,58 and combinations of aerosol boxes and plastic wraps (eight reports). 6,8,13,15,32,37,43,49 Eleven reports included other types of barrier enclosures (modified incubator hood, 7 carton box, 8 acrylic panels, 50 surgical retractors, frames and anaesthetic poles, 21,42,44,48 external fixators, 14 suspension laryngoscopy support, 41,55 and modified packaging tray 40 ). In 10 cases, a smoke evacuator/aspirator was reported.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…5,6,8e11,13,14,17e21,23,25e27,29e31,33,40,41,46,48,52,53,57,58 Cases of barrier-enclosure use with one mannequin or one human were noted in eight reports, 12,15,16,42,50,54,62,63 five cases in three reports, 22,24,44 and series of 25 or more cases in three reports. 37,45,47 The reported settings were simulations with mannequins in 20 cases, 4e6,11e13, 16,19,21e23,25e28,39,41,45,49,60 simulations with study volunteers in two cases, 9,51 use in adult patients in 11 cases, 7,15,23,27,31,37,42,44,47,50,55 and four in paediatric patients. 41,43,52,56 In 24 reports, there was either no setting described or there was a barrier-enclosure description without demonstration.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other measures included geographically segregating OR complexes to reduce cross-infection, reducing humidity level and temperature of ORs to reduce HCW perspiration, and using plastic drapes around the tracheostomy operative field to create a closed sterile environment. 40,42,43 A summary of protection measures is provided in Table 4. All studies which implemented more than 3 of the listed measures and also reported on HCW outcomes had an infection rate of 0% among HCW.…”
Section: Protection Measures During Outbreaksmentioning
confidence: 99%
“…Chow et al conducted ve tracheotomies using two horizontal anaesthetic screens and a clear sterile plastic sheet draped over the operative eld.This helped create a closed sterile environment,preventing droplet infection,aerosol contamination and viral transmission.Droplet contamination was most severe over the central surface of the plastic sheet overlying the site of operation.In this way use of face shields may be spared as it gives rise to fogging and also hinders the use of a head light while operating [36].…”
Section: Tracheotomymentioning
confidence: 99%